Designing and shaping lessons that develop students' mathematical abilities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Designing and shaping lessons that develop students' mathematical abilities is a complex and multifaceted process that requires a deep understanding of both the theoretical foundations of pedagogy and the specifics of mathematical thinking. In the conditions of modern educational space, where the emphasis is shifting towards the development of critical thinking, creativity and the ability to solve problems independently, the creation of such training programmers that not only impart knowledge, but also stimulate the intellectual growth of students is of particular importance.